Lacticaseibacillus paracasei K56 inhibits lipid accumulation in adipocytes by promoting lipolysis - Silu Wang; Jinxing Li; Wei-Hsien Liu; Niya Li; Huijing Liang; Weilian Hung; Qiuyue Jiang; Ruyue Cheng; Xi Shen; Fang He (Food Science and Human Wellness)
Probiotics crosstalk immunity to improve host glycolipid metabolism, which is a new strategy for obesity. This study aimed to explore the functions of Lacticaseibacillus paracasei K56 (K56), in regulating the lipid metabolism of adipocytes and its immune regulation mechanisms. We co-cultured RAW264.7 macrophages with K56, and the K56-stimulated RAW264.7-conditioned medium (K56-CM) was collected and treated with 3T3-L1 pre-adipocytes. The expression of lipid metabolism-related markers of adipocytes, and the content of cytokines in CMs were detected. The results demonstrated that K56-CM promoted the expression of peroxisome proliferator-activated receptor-γ (PPAR-γ), CCAAT/enhancer binding protein α (C/EBPα), and other adipogenesis-related markers, which resulted in the upregulation of lipolysis markers, such as hormone-sensitive lipase (HSL), adipose triglyceride lipase (ATGL). The activation of lipolysis enhanced the expression of fatty acid β-oxidation-related and mitochondrial biogenesis-related markers and reduced lipid accumulation in adipocytes. The glycolipid metabolism pattern of K56 may be due to its immunomodulatory characteristics, which stimulated macrophages to secrete fewer TNF-α, thereby promoting the expression of lipolysis-related markers, and TNF-α synergized with lipase to promote lipolysis. It has not been reported that L. paracasei modulated lipid metabolism via the lipolysis pathway, which suggested that K56 may regulate glycolipid metabolism of the host by maintaining immune homeostasis.